Helminthiasis in school-age children from Gresik, East Java, Indonesia - Utomo B.; Fatmaningrum W.; Sulistiawati; Fauziyah S.; Sucipto T. H.; Adnyana I M. D. M.; Eljatin D. S.; Fadhilah N.; Novitasari A. E.; Al-Talib H. (Helminthologia)
This study aims to investigate the soil-transmitted helminth infection among school-age children in Gresik, East Java, Indonesia. An analytical observational study with a cross-sectional design was conducted from July to November 2023 in selected elementary schools in Gresik, East Java, Indonesia. Logistic regression analysis was employed to assess the impact of each risk factor on the likelihood of infection transmission. A total of 183 school-age children were screened for the occurrence of helminth eggs in their feces. Twenty-two feces samples from 183 children were positive for helminth egg, consisting of 14 children infected by Ascaris lumbricoides (6.36 %), 3 children infected by Trichuris trichiura (1.304 %), 3 children infected by Oxyuris vermicularis (1.304 %), and 3 children infected by Hookworm (1.304 %). The highest prevalence was found in 7-year-old children (31.8 %). Children who pulled off shoes while in school were more likely to be infected with an overall OR of 8.392 (95 % CI 1.63 – 43.65). Children who played in the dumpsite were more likely to be infected with an overall OR of 4.521 (95 % CI 0.578 – 31.28). Children who washed before eating were more likely to be infected with an overall OR of 3.579 (95 % CI 0.587 – 21.835). Therefore, to lessen the prevalence of STHs among school-age children in Gresik, we recommend improving hygiene conditions in schools. The government should prioritize enrolling all primary schools in hygiene classes as the school health program.